Computational structure analysis of coronavirus ion channels thermodynamic stability with evolutionary divergence - Ng, Linus Kah Way (Nanyang Technological University, 2020)
Pandemic caused by novel SARS-CoV-2 has brought about much change in how society works. With little understanding of the virus, treatments are far and few between. Research has uncovered major contribution by viral ion channel proteins, mainly 3a and E, to viral virulence. Thus, inhibition of these proteins is one viable therapeutic strategy. However, current variants having poor thermostability hinders structural inhibition studies. Selecting variants that are closer to ancestral sequences with potentially better thermostability is an approach to circumnavigate this issue. Computational analyses were employed to determine the correlation between evolutionary divergence and thermostability. Results illustrate that between viroporins 3a and E, the former is of better protein structure with more pairwise interactions and with little conformational variations. Through possible functionality and thermostability trade-off, E has reduced thermostability with evolution, although the ion channel itself displays opposing results. Protein 3a follows the trend of E protein ion channel with increasing thermostability through evolution. Hence, selecting variants closer to ancestral sequences might help structural studies but only for E proteins.